The inner ear proteome of fish. (21st December 2018) - Thomas, Oliver R. B.; Swearer, Stephen E.; Kapp, Eugene A.; Peng, Po; Tonkin‐Hill, Gerry Q.; Papenfuss, Anthony; Roberts, Anne; Bernard, Pascal; Roberts, Blaine R.
Abstract : The mechanisms that underpin the formation, growth and composition of otoliths, the biomineralized stones in the inner ear of fish, are largely unknown, as only a few fish inner ear proteins have been reported. Using a partial transcriptome for the inner ear of black bream ( Acanthopagrus butcheri ), in conjunction with proteomic data, we discovered hundreds of previously unknown proteins in the otolith. This allowed us to develop hypotheses to explain the mechanisms of inorganic material supply and daily formation of growth bands. We further identified a likely protein mediator of crystal nucleation and an explanation for the apparent metabolic inertness of the otolith. Due to the formation of both daily and annual increments, otoliths are routinely employed as natural chronometers, being used for age and growth estimation, fisheries stock assessments, and the reconstruction of habitat use, movement, diet and the impacts of climate change. Our findings provide an unprecedented view of otolith molecular machinery, aiding in the interpretation of these essential archived data. Abstract : Otoliths are biomineral structures required for hearing and balance in fish. They are used in ecological research and to investigate biomineralization processes. In this study, we discovered hundreds of proteins previously unknown to be associated with otoliths, providing new insights into the likely mechanisms involved in their formation and growth. Our results have broad implications for biomineralization processes in general.